IGF2BP2 Induces U251 Glioblastoma Cell Chemoresistance by Inhibiting FOXO1-Mediated PID1 Expression Through Stabilizing lncRNA DANCR - Han, Junfei; Yu, Xiaojun; Wang, Shanxi; Wang, Yingguang; Liu, Qikun; Xu, Haoran; Wang, Xiaosong (Frontiers in Cell and Developmental Biology, 2022)
Glioma is the most common type of malignant tumor of the nervous system and is characterized by high mortality and poor outcome. This study aims to investigate the mechanism underlying IGF2 mRNA-binding protein 2 (IGF2BP2) and long noncoding RNA DANCR in etoposide resistance of glioblastoma (GBM) cells. Bioinformatics analysis identified the IGF2BP2-related regulators and DANCR target genes, which were subsequently evaluated by RNA pull-down and RIP assays. We exposed GBM cells to etoposide and thus established etoposide-resistant cells. Through functional experiments, we evaluated the interrelationship among IGF2BP2, DANCR, phosphotyrosine interaction domain containing 1 (PID1), and forkhead box protein O1 (FOXO1) and further assessed their impact on the sensitivity of GBM cells to etoposide. IGF2BP2 and DANCR were highly expressed in glioma cells and tissues, whereas PID1 and FOXO1 were poorly expressed. Mechanistically, overexpression of IGF2BP2 promoted DANCR stability and reduced DANCR methylation, whereas silencing of IGF2BP2 reduced survival of GBM cells and etoposide-resistant cells. Besides, DANCR interacted with FOXO1 to promote the ubiquitination of FOXO1. FOXO1 promoted the transcriptional expression of PID1, enhancing the chemotherapy sensitivity of GBM cells, but overexpression of PID1 reversed the impact of IGF2BP2. Collectively, IGF2BP2 inhibits PID1 expression through the DANCR/FOXO1 axis, inducing drug resistance in GBM cells, and promoting glioma progression.